Desenho e Construção de um protótipo gerador de jato de plasma frio a pressão atmosférica para aplicações biomédicas - Nascimento Neto, Arlindo Balbino do (2014)
Research for better performance materials in biomedical applications are constants. Thus recent studies aimed at the development of new techniques for modification of surfaces. The low pressure plasma has been highlighted for its versatility and for being environmentally friendly, achieving good results in the modification of physic chemical properties of materials. However, it is requires an expensive vacuum system and cannot able to generate superficial changes in specific regions. Furthermore, it is limits their use in polymeric materials and sensitive terms due to high process temperatures. Therefore, new techniques capable of generating cold plasma at atmospheric pressure (APPJ) were created. In order to perform surface treatments on biomaterials in specific regions was built a prototype capable of generating a cold plasma jet. The prototype plasma generator consists of a high voltage source, a support arm, sample port and a nozzle through which the ionized argon. The device was formed to a dielectric tube and two electrodes. This work was varied some parameters such as position between electrodes, voltage and electrical frequency to verify the behavior of glow discharges. The disc of titanium was polished and there was a surface modification. The power consumed, length, intensity and surface modifications of titanium were analyzed. The energy consumed during the discharges was observed by the Lissajous figure method. To check the length of the jets was realized with Image Pro Plus software. The modifications of the titanium surfaces were observed by optical microscopy (OM ) and atomic force microscopy (AFM ). The study showed that variations of the parameters such as voltage, frequency and geometric position between the electrodes influence the formation of the plasma jet. It was concluded that the plasma jet near room temperature and atmospheric pressure was able to cause modifications in titanium surface